2022
DOI: 10.11604/pamj.2022.41.167.31535
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of male partner involvement in antenatal care services in eastern Kenya: a cross-sectional study

Abstract: Introduction male partner involvement in antenatal care (ANC) contributes to improved maternal health outcomes, but has been wanting in sub-Saharan Africa. We investigated the prevalence and factors associated with male involvement in ANC. Methods this was a cross-sectional survey conducted in November and December 2019 in Kitui East sub-county, Kenya. We recruited men above 18 years whose spouses had given birth 12-months prior to the study. Data were collected at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In spite of these enormous available evidence, studies have reported low male attendance and involvement in maternal and child health departments in Kenya [ 8 - 10 ]. A Kenyan National Survey and an Eastern Kenyan study revealed that about 30% and 23% of men respectively accompany their spouses and or wives to the MCH clinic [ 8 , 9 ]. Several barriers have been cited that impede men from accompanying their spouses to the MCH department.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these enormous available evidence, studies have reported low male attendance and involvement in maternal and child health departments in Kenya [ 8 - 10 ]. A Kenyan National Survey and an Eastern Kenyan study revealed that about 30% and 23% of men respectively accompany their spouses and or wives to the MCH clinic [ 8 , 9 ]. Several barriers have been cited that impede men from accompanying their spouses to the MCH department.…”
Section: Introductionmentioning
confidence: 99%
“…32 On the other hand, previous ANC experience also impacts men's involvement in ANC. 34 Based on our research, the prevalence of PTB is higher than other adverse birth outcomes. This was possibly due to inaccuracy in reporting the LMP.…”
Section: Discussionmentioning
confidence: 64%
“…It has been found from this study that as the age of the men is increasing, a greater proportion of husbands are not availing ANC check-ups because their wives have already given birth to children. This is supported by the findings of studies that highlighted the fact that the participants who had less than four children were more likely to be involved in ANC compared to those with five or more children (Chamos et al, 2022;Nyamai et al, 2022;Sarvar & Sonavane, 2018). Kassahun et al (2018) opined that being from rural residences increases the likelihood of not availing ANC services.…”
Section: Discussionmentioning
confidence: 79%